Follow-Up Study of Over Three Years of Patients with Uveitis after Cataract Phacoemulsification: Outcomes and Complications. (1st November 2016) - Abbouda, Alessandro; Tortorella, Paolo; Restivo, Lucia; Santoro, Elisa; De Marco, Federica; La Cava, Maurizio
ABSTRACT: Purpose : To evaluate the rate and onset of intraoperative and postoperative complications post-phacoemulsification. Methods : One hundred sixty-two eyes of 145 patients with uveitis who underwent phacoemulsification between 2006 and 2009 were identified through surgical record review. Fifty-nine eyes of 46 patients met the inclusion criteria. Hazard ratio (HR) and Kaplan-Meier survival probability were calculated for each class of uveitis. Results : Macular edema (ME) resulted to be associated to chronic postoperative inflammation ( r = 0.6; p = 0.00) and mostly related to patients who presented more than one postoperative relapse/year ( r = 0.2; p = 0.02). Fuchs uveitis resulted to be a risk factor for posterior capsule opacification (PCO) (HR 3.36 IC95%1.0-10.5; p = 0.03). Hypotony and elevated intraocular pressure (IOP) were detected in the anterior uveitis group (0.02 EY). Conclusion : The HR to develop ME was significantly related to chronic anterior uveitis. PCO and elevated IOP are most frequent in Fuchs uveitis. The postoperative visual acuity result was good among all the uveitis groups.